2016
DOI: 10.21608/zvjz.2016.7877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Inclusion of Sunflower Meal on Performance, Carcass Traits, Litter Moisture and Economic Efficiency of Broiler Chickens

Abstract: An experiment was designed to investigate the influence of different levels of dietary inclusion of sunflower meal on broiler's productive performance, serum lipid profile, carcass traits, litter moisture and economic efficiency. One hundred and twenty, day-old Cobb broiler chicks were assigned randomly into 5 equal groups, each contained 24 chicks in three replicate pens (8 chicks/pen). Group 1 was fed on basal diet without sunflower meal and kept as a control group, while groups from 2 to 5 were fed on diets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
1
3
1
Order By: Relevance
“…Based on economic efficacy indicators such as feed cost/ TC, TR/TC, NP/TC, TC/TR, and NP/TR, when SFM or RSM are incorporated into the diet resulted in better results than the control group as they had lower feed costs and TC with higher TR and NP. It is consistent with the outcomes of Kamel et al [79] and Attia et al [80] who found that adding non-conventional feed resources to quail diets increased their efficiency.…”
Section: Discussionsupporting
confidence: 91%
“…Based on economic efficacy indicators such as feed cost/ TC, TR/TC, NP/TC, TC/TR, and NP/TR, when SFM or RSM are incorporated into the diet resulted in better results than the control group as they had lower feed costs and TC with higher TR and NP. It is consistent with the outcomes of Kamel et al [79] and Attia et al [80] who found that adding non-conventional feed resources to quail diets increased their efficiency.…”
Section: Discussionsupporting
confidence: 91%
“…The result of this study disagree with Fiky et al, (2020) they showed that adding linseed or sunflower oils have significantly (P ≤ 0.05) increased cholesterol value at 5 weeks of ages. The obtain result disagree with Attia et al, (2016) they noted that the dietary intake of different levels of sunflower meal did not reveal any significant difference (P>0.05) in the measured serum lipid parameters (total lipid, total cholesterol, high, low and very low density lipoprotein cholesterols. Even if the diet had no effect on VLDL and HDL plasma levels, the finding of higher plasma total cholesterol and phospholipids levels in chickens fed the low lipid diet compared with chickens fed the high lipid diet suggests that the lipid composition of lipoproteins was affected by the dietary energy source as diets were isoenergetic and isoproteic and had no effect on the amount of feed ingested ( Baéza et al, 2015)…”
Section: Serum Lipid Profilecontrasting
confidence: 89%
“…Nevertheless, there are many cases in which enzyme supplementation to SFM containing diets did not improve of all studied growth parameters [6,[27][28][29]. In some instances, exogenous enzymes use resulted in worse performance parameters [26], whereas in some studies, including ours, it resulted in improved growth performance parameters [16,[22][23][24]30]. Such discrepancies in the results recorded in literature are multifaceted, and may be attributed to the quality of SFM processing, variety of experimental birds, experimental periods (21, 35 or 42 d), and diet composition [30].…”
Section: Discussionmentioning
confidence: 95%
“…[23] reported that SFM can be used up to 20% in growing quail diets without negatively affecting performance. In their study [24], postulated that the inclusion of SFM at higher levels may necessitate the need of supplementation with synthetic lysine and oils in the diet in-order to compensate for the low metabolizable energy (ME) associated with this ingredient. However, supplementation with extra fats to rectify the low ME associated with SFM use must be done with caution, and huge attention in terms of fats storage must be exercised due to rancidity and poor pelleting quality; which may in turn necessitate the need for additional supplementation with antioxidants [14,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation